Sugarcane bagasse: a potential of low cost biosorbent for removal of heavy metals from water / Zildawarni Irwan ... [et al.] - Irwan, Zildawarni; Wan Kamarudin, Wan Farahiyah; Abdullah, Mardhiah; Faizal, Muhammad Aqil Firdaus; Mohamad Yamin, Muhammad Azrin; Nordin, Farah Nur Syahira; Ismail, Nor Azrina Natasya (2021)
Water pollution is a major environmental problem faced by modern society that leads to ecological disequilibrium and health hazards. Heavy metals can enter a water supply by industrial and consumer waste, or even from acidic rain breaking down soils and releasing heavy metals into streams, lakes, rivers, and groundwater causing water pollution. Heavy metal ions such as copper, cadmium, lead, nickel, and chromium, often found in industrial wastewater, present acute toxicity to aquatic and terrestrial life, including humans. Thus, the discharge of effluents into the environment is a chief concern. Active carbon has been frequently used as an adsorbent, but it remains as an expensive material. Therefore, there is an urgent needfor all possible sources of agro-based inexpensive adsorbents. In this study, our objective is to study the preparation of natural adsorbent heavy metal from sugarcane bagasse and investigate the effectiveness of sugarcane bagasse as a natural adsorbent to remove copper from wastewater. Adsorption processes are being widely used by various researchers for the removal of heavy metals from waste streams. Therefore, a methodology is developed for the removal of ion metal copper (Cu2+) from its aqueous solution using sugarcane bagasse as filter paper. Samples were analyzed by the technique of the Inductively Coupled Plasma Mass Spectrometry (ICP-MS). The result showed that the preparation of filter paper out of sugarcane bagasse was successfully obtained.